Impact of Human Resource Management (HRM) Practices on the Performance of Call Center in Lahore, Pakistan; Evaluating Employee Staffing, Satisfaction and Reward - Humira Mirza; Waqar Ahmed; Yasim Tasleem (Governance and Society Review, 2024)
The achievement of effective Human Resource Management (HRM)practices significantly influencesthe performance of an organization.The current studyaimedto investigatethe impact of HRM practices,such as employee staffing, employee satisfaction,and employee reward on employee performance in Lahore, Pakistan. Data was gathered through the survey methodby using the sample size of 306. The response was analyzed by using Statistics Package for SocialSciences (SPSS). SPSS is used tomeasurethe relationships through regressionanalysis, descriptive analysis, model summary, and Analysis of Variance (ANOVA). Findings revealedthat the HRM practices play a crucial role toimprovethe performanceof organizations in Lahore, Pakistan. Resultsexpend that addressing employeestaffing, employee satisfaction,and rewards wouldhelp toimprovethe performanceof call centers. Moreover, the study also recommendedthe strategies involvingthe deploymentof Artificial Intelligence (AI)-powered work force management,software and staffing, and real-time performance analyticsto enhance transparency and coaching